2018
DOI: 10.1126/sciadv.aat5895
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a low-temperature dynamical transition in concentrated microgels

Abstract: The dynamical transition of hydrated proteins also occurs in nonbiological macromolecules, such as colloidal microgels.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 45 publications
10
67
0
Order By: Relevance
“…For such very dense regime, we recently reported an investigation of the dynamical behavior of PNIPAM microgels at low temperatures, well below room temperature. By means of neutron scattering experiments and numerical simulations, it was found that the low-temperature evolution of the mean square displacement (MSD) of the polymer atoms shows a slope change at a temperature T C 250 K, due to the onset of anharmonic motions [23]. This phenomenon in microgels is similar to the known dynamical transition observed in proteins [24,25] and appears to be strongly driven by PNIPAM-water interactions [26].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For such very dense regime, we recently reported an investigation of the dynamical behavior of PNIPAM microgels at low temperatures, well below room temperature. By means of neutron scattering experiments and numerical simulations, it was found that the low-temperature evolution of the mean square displacement (MSD) of the polymer atoms shows a slope change at a temperature T C 250 K, due to the onset of anharmonic motions [23]. This phenomenon in microgels is similar to the known dynamical transition observed in proteins [24,25] and appears to be strongly driven by PNIPAM-water interactions [26].…”
Section: Introductionmentioning
confidence: 85%
“…For c ≥ 43 wt%, data were normalized to 1 at T = 0 K using the low-temperature measurements reported in Ref. [23]. Upon heating, the integrated elastic intensity of the hy -FIG.…”
Section: All-atom Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Swelled PNIPAM microgels synthesized with the original method [6] have a diameter of hundreds of nanometers and display a heterogeneous structure, with a dense core and a looser external region of the particle. The internal nano-structure is suitable to confine molecular entities, such as enzymes or reactants, to promote chemical processes in a selective modality [7] and also to prevent ice nucleation [8,9]. By exploiting the temperature sensitivity of the polymer chain conformation across the volume phase transition temperature (VPTT), the architecture of the network can be reversibly adapted.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a regular dynamical transition was observed for the first time in a nonbiological macromolecule. 319 This offers the possibility to study a wider array of pressure-vitrified macromolecule solutions. If a low temperature dynamical transition would be observed independently of the chemical nature of the macromolecule this transition is highly likely related to the unique behavior of water alone.…”
Section: Discussionmentioning
confidence: 99%